Risk Factor Analysis of Carpal Tunnel Syndrome Complaints Among Informal Sector Tailor Workers in Cimahi City - Sandra Amalia; Yuliani Setyaningsih; Suroto Suroto (Journal of Social Research, 2025)
Carpal tunnel syndrome (CTS) is a prevalent musculoskeletal disorder resulting from compression of the median nerve in the wrist, leading to symptoms such as pain, tingling, and weakness in the hands. Workers in the informal sector, particularly tailors, are at significant risk due to repetitive hand movements, prolonged static postures, and suboptimal ergonomic conditions. This study aims to analyze the occupational risk factors associated with CTS complaints among informal sector tailors in Cimahi City, focusing on age, smoking habits, and working hours. Using a cross-sectional design, data were collected from 107 tailor respondents through purposive sampling and assessed via structured questionnaires. The findings revealed a statistically significant association between age and CTS complaints (p-value = 0.001), indicating that older workers are more susceptible to the disorder. However, no significant correlation was found between smoking habits and CTS complaints (p-value = 0.269). Conversely, a strong association was identified between working hours and CTS complaints (p-value = 0.001), suggesting that prolonged working time increases the risk of developing symptoms. This research contributes valuable insights into occupational health risk factors for tailors, emphasizing the need for improved workplace ergonomics and targeted preventive interventions.